Change Management and Operational Efficiency of Plant Contractors in the Amata Nakorn Industrial Estate, Chonburi Province - Pongmungpak, Pondchai; Pimoljinda, Tanawat; Siripraserdchok, Rittikron (Ratchaphruek Journal, 2015)
Change management and operational efficiency of plant contractors in the Amata Nakorn Industrial Estate, Chonburi Province. The main purpose is to study of relationship between change management approaches to effectively operate the organization as a contractor in the dynamics of plant in the Amata-Nakorn Industrial Estate, Chonburi province. In this study, the sample studied was 56 contractors at the plant in the Amata-Nakorn Industrial Estate, Chonburi province, using a simple random sampling method. The researcher used the questionnaires as a tool for data collection. The results found that the important factors that cause the change, and showed the less-focus overview of the issue. The overviews of change management approach and efficiency in the operation in each issue were in high levels. Approach to change management was related to the performance of the operation of the contractors in Amata Nakorn Industrial Estate, Chonburi province which showed correlation coefficient analysis statistically significant at.05